The Power of Fancy: Liberty and Imagination in Philip Freneau's College Writings - Álvaro Albarrán Gutiérrez (Miscelánea: A Journal of English and American Studies)
Like other prominent members of the revolutionary generation, Philip Freneau lived his formative years against the backdrop of the imperial crisis that would lead to the independence of the US in 1776, and this would make a lasting impression on his later life and writings, especially as regards his ideas on the possibility for creativity and individuality in a time of increasing politicisation. This article examines the particular terms in which the poet’s college experiences influenced his conflicted take on liberty and imagination, which remained a persistent concern both during and after his time at the College of New Jersey (now Princeton). Drawing on original archival work, the article focuses on his most extensive reflection on the matter, “The Power of Fancy” (1770), and offers an analysis of the poem in connection with several other prominent eighteenth-century philosophical and literary texts that also address the imaginative faculty. In so doing, the article reveals the workings of an anti-imaginistic tradition, instilled through the curriculum of late-colonial Princeton, in Freneau’s college writings — a tradition that the poet both espoused and resisted on his quest for individual autonomy and creative expression.